2017
DOI: 10.1371/journal.pone.0182013
|View full text |Cite
|
Sign up to set email alerts
|

The relations between sleep, time of physical activity, and time outdoors among adult women

Abstract: Physical activity and time spent outdoors may be important non-pharmacological approaches to improve sleep quality and duration (or sleep patterns) but there is little empirical research evaluating the two simultaneously. The current study assesses the role of physical activity and time outdoors in predicting sleep health by using objective measurement of the three variables. A convenience sample of 360 adult women (mean age = 55.38 ±9.89 years; mean body mass index = 27.74 ±6.12) was recruited from different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 55 publications
(76 reference statements)
2
38
1
1
Order By: Relevance
“…This could mean that addressing mental and physical health problems may only have a rather minimal effect on improving sleep in people who are sedentary, and that the link between sedentary behaviour and sleep problems may be better explained by other pathophysiological mechanisms. For example, it is known that being physically active instead of being sedentary is implicated in a range of physiological changes, including potential alterations of circadian rhythms (Aoyama & Shibata, ; Murray et al., ). Being active may acutely (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This could mean that addressing mental and physical health problems may only have a rather minimal effect on improving sleep in people who are sedentary, and that the link between sedentary behaviour and sleep problems may be better explained by other pathophysiological mechanisms. For example, it is known that being physically active instead of being sedentary is implicated in a range of physiological changes, including potential alterations of circadian rhythms (Aoyama & Shibata, ; Murray et al., ). Being active may acutely (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the relationship between physical activity and sleep is influenced by underlying neurobiological mechanisms which were not assessed in the current study. For example, it is known that exercise, or a structured form of physical activity, is implicated in a range of physiological changes, including potential alterations of circadian rhythms [49,50]. Several studies have observed that moderate to vigorous intensity exercise may acutely (i.e., within minutes) alter melatonin levels and result in a shift of the onset of nocturnal melatonin.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…A C C E P T E D ACCEPTED MANUSCRIPT [53]. Other factors to consider include time spent outdoors [50] and light exposure [54] as potentially moderating the association between physical activity levels and presence of sleep problems via circadian-driven aspects of sleep. However, to the best of our knowledge no previous study on the effects of a physical activity intervention on sleep outcomes has tested, or controlled for, increased exposure to light arising from increased time spent being physically active outdoors.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…18:01-24:00 based on previous studies [13,19,20]. We calculated the percentage of the three time intervals of MVPA engagement for each participant.…”
Section: Exposure Variablesmentioning
confidence: 99%